Environmental factors affecting the distributions of the native Eurasian beaver and the invasive North American beaver in Finland - Alakoski Riikka; Kauhala Kaarina; Tuominen Sakari; Selonen Vesa (ELSEVIER SCI LTD, 2022)
When planning conservation and reintroductions of native species and control of invasive species, it is important to understand the environmental factors affecting species distributions. Habitat suitability largely determines where species can occur, but in addition to habitat and food resources, it is important to also consider human disturbance and climate when mapping possible distributions. We studied the environmental factors affecting the present distribution of the native Eurasian beaver (Castor fiber) and the invasive North American beaver (C. canadensis) in Finland. We compared the role of food resources, aquatic habitat type, anthropogenic disturbance and climate for beaver occurrence with species distribution models. We created maps of suitable areas for the two species and compared how the results would change if these two ecologically similar species were modelled together. We found that aquatic habitat type and climate largely explain the present distributions of the species. In addition, there were differences between the species in their preference for food resources, aspen, birch and grey alder. However, we suspect that the species' reintroduction history, i.e. the differences in the present environment, much explain the differences found between the species. We conclude that when planning possible reintroductions for the Eurasian beaver, factors other than food resources should also be considered. We also suggest that studies on habitat suitability should consider the history of the species and include data from different environments. Thus, more comprehensive information for management planning would be achieved and a better ability to predict the location of optimal areas for the species.